EVENTS AFTER THE REPORTING DATE: BENCHMARKS MATERIALITY FOR ACCOUNTING - I. V. Bardina (Вестник университета)
Arguments and justification of obligatory development and statements in accounting policy of the organization for the purposes of accounting of level of materiality and its control indicators for accounting of events after reporting date have been presented. These events are implemented between the end of the reporting period and the date of signing of the financial statements for the reporting calendar year and can have a significant impact on the financial condition, financial results and monetary circulation of the organization. The influence of these events is uncertain and difficult to assess objectively. Especially this impact affects their materiality.